Nurses' Knowledge about Diabetes Foot Ulcer Prevention and Treatment: An Integrative Review - Hasdi, Hasdi; Syahrul, Syahrul; Yusuf, Saldy (Faculty of Nursing, Universitas Hasanuddin, 2022)
Introduction: Diabetic Foot Ulcer (DFU) is a complication often experienced by patients with Diabetes Mellitus (DM). Evidence-based prevention and treatment in DM patients who are at risk of DFU can reduce the global economic burden. Nurses' knowledge plays an important role in screening, prevention, and proper treatment of DFU. This review identifies evidence of nurses' knowledge about the prevention and treatment of DFU and identify factors related to nurses' knowledge. Method: The study applied an integrative review design. The relevant literature were searched from PubMed, CINAHL (EBSCO), Wiley Online Library, ScienceDirect, and ProQuest. The inclusion criteria was articles published in English, peer-reviewed articles, and journals between January 2016 and May 2021, by using keywords; “nurs*”, “diabetic foot*” “knowledge”,